The Defence of Necessity in International Law and Investor Versus State Dispute Settlement - AlModarra Bader Bakhit M (Journal of Legal Studies, 2019)
The ability of foreign investors to sue host states without reliance on diplomatic protection is one of the most important developments in international investment law in the post-World War II era. The rise of investor-state dispute settlement under international regimes like the Convention Establishing the International Centre for the Settlement of Investment Disputes (ICSID Convention) raises some concerns from states regarding loss of sovereignty. However, there are defences available to states when they intervene in their economies for purposes like public utility or the need to safeguard an essential interest. Thus in spite of treaty commitments that bind states to protect the investments of foreign investors within their domains, there are available defences for their intervention in their economies even if such interventions become inimical to the interests of foreign investors and could, prima facie, raise the possibility of infringements of the rights of foreign investors. One of such defences available to states is the principle of necessity. This article explores the principle of necessity in international law and how it operates as a defence for states in investor-state dispute settlement. It also conducts analysis of the Annulment Decision in the CMS v Argentina case to shed light on the principle of necessity.